Influences of the economic and financial crisis on the jurisprudence of the Court of Justice of the European Union on social rights - Zezza, Michele (2023)
The main purpose of the paper is to reflect on the meaning and the function of social rights within the EU system, in the current scenario dominated by the global economic and health crisis, paying particular attention to their relationship to the limits imposed by budgetary restrictions. Using some methodological tools of legal theory, we propose to analyse certain constitutive aspects of the legal reasoning developed by the European Court of Justice with respect to social rights.